MANIFESTASI HEROISME DALAM TRADISI JEPANG DAN JAWA Persamaan dan Perbedaan Dongeng Momotarō dan Epos Bharatayuda - Fajria Noviana (IZUMI, 2014)
Abstract This comparative study was conducted to find out how heroism in Japanese and Javanese traditions is manifested into two literary works representing those traditions:  Momotarō and Bharatayuda. This study is also aimed to find out the similarities of heroism manifestation in the two traditions. The reason for conducting this study is from the assumption that heroism is a universal concept. Therefore, such heroisms have similarities although they may come from different traditional backgrounds. Structural analysis and binary opposition were used in this study. The structural analysis was used to obtain the data on traditional background of the areas and the actions done by the main characters, while binary opposition was used to obtain the data on the main characters’ heroic actions which were then concluded as the heroic manifestation. The result shows that the heroismmanifestation in Japanese and Javanese traditions has the following things in common: 1) conquering enemies, 2) protecting the members of the group, 3) keeping promise, 4) recompense, and 5) acting ethically. The result of this study can also prove the truth of the assumption.  Key words: heroism, heroic actions, Japanese and Javanese traditions